Inferential profiles emerging from reading for summarization and reading for translation tasks: an exploratory study - Winfield, Claudia Marchese (2014)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2014.